2019
DOI: 10.31703/gpr.2019(iv-i).06
|View full text |Cite
|
Sign up to set email alerts
|

Pakistan's General Elections of 2018: Representation of Economic Issues and Orientation of Political News Coverage in The Elite Newspapers of Pakistan

Abstract: In a democratic society, mass media and political system have a strong bond with each other. Big media powerhouses attempt to develop linkages with political parties for economic benefits. These parties' linkages with media houses may have affected news items' representation of issues from both positive and negative reporting angles. An eminent scholar of agenda-setting through McCombs et al. (1997), pointed out that media has great power to set the agenda of public and political parties also actively engages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study utilizes a quantitative content analysis to codify data of disclosure on participation in health programs and/or medical research. Prior studies have concluded that quantitative content analysis is more transparent and permits the replicability of the research design, compared to qualitative content analysis [41]. Quantitative content analysis can be conducted through equal and unequal weighting ratings.…”
Section: Results: Health-related Csrd Analysismentioning
confidence: 99%
“…This study utilizes a quantitative content analysis to codify data of disclosure on participation in health programs and/or medical research. Prior studies have concluded that quantitative content analysis is more transparent and permits the replicability of the research design, compared to qualitative content analysis [41]. Quantitative content analysis can be conducted through equal and unequal weighting ratings.…”
Section: Results: Health-related Csrd Analysismentioning
confidence: 99%